2,5-dioxido-1,4-benzoquinonediimine (H2L2-), a hydrogen-bonding noninnocent bridging ligand related to aminated topaquinone: different oxidation state distributions in complexes [(bpy)(2)Ru(2)(mu-H2L)](n) (n=0,+,2+,3+,4+) and [(acac)(2)Ru(2)(mu-H2L)] - Kar, S.; Sarkar, B.; Ghumaan, Sandeep; Janardanan, D.; van Slageren, J.; Fiedler, Jan; Puranik, Vedavati G.; Sunoj, R. B.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Chemistry - a European Journal, 2005)
{The symmetrically dinuclear title compounds were isolated as diamagnetic [(bpy)(2)Ru(mu-H2L)Ru(bpy)(2)]- (ClO4)(2) (1-(ClO4)(2)) and as paramagnetic [(acac)(2)Ru(mu-H2L)Ru(acac)(2)] (2) complexes (bpy = 2,2'-bipyridine; acac(-) -
Keywords: bridging ligands; Density functional calculations; EPR spectroscopy; N; O ligands; ruthenium

Selective synthesis of N,N-dimethyl aniline derivatives using dimethyl carbonate as a methylating agent and onium salt as a catalyst - Shivarkar, A. B.; Gupte, S. P.; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A - Chemical, 2005)
N-Alkylation of anilines by dimethyl carbonate (DMC) catalyzed by onium salts has been demonstrated. The work presented here shows that a simple catalytic system consisting of onium salts in the presence of a small amount of water is extremely effective in enhancing the DMC mediated N-alkylation of anilines to dialkylated products. The effect of reaction conditions on the synthesis of N,N-dimethyl aniline (NNDMA) from aniline and DMC has been investigated. Under the optimized conditions highest yield of NNDMA obtained was 99.8%, which is the best reported for liquid phase N-alkylation of aniline using DMC. The role of water in enhancing the yield of NNDMA is explained and a reaction-networking scheme is constructed, which summarizes the chemistry behind liquid phase N-alkylation of anilines by DMC. The catalyst has been shown to recycle up to five times and at the end of fifth recycle almost 98% of NNDMA yields were obtained. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Aniline; Dimethyl carbonate; methylation; N; N-alkylation; N-dimethyl aniline; onium salts